Modeling and simulation of metal organic halide vapor phase epitaxy (MOHVPE) growth chamber - Annuar, N.Z.M.; Sabri, M.F.M.; Bakar, A.S.A. (Springer Verlag (Germany), 2014)
Over the last few decades, there was a substantial appeal on the growth of gallium-nitride (Ga-N) based alloy for high performance optoelectronic devices such as blue/violet laser diode, blue/white light emitting diode etc. In the recent years, there have been revolutionary changes in semiconductor field. Growth method for GaN-based film has been extensively explored, with success of thick film growth using halide vapor-phase epitaxy technique. The theoretical changes were attributed from the experimental results where modeling was vastly used for the purpose of design of equipment. This is because of the cost of the equipment and it is one of the major burdens in semiconductor processing. This process constitutes an important technology for manufacturing thin solid film in the semiconductor industry. To address these issues, a new development called metal organic halide vapor phase epitaxy (MOHVPE) reactor has been proposed in this study. Modeling with five inlet nozzles with 54 cm long is designed by design software. The numerical study of horizontal MOHVPE growth shows dependence on temperature and species flow rates. The inlet area is set to room temperature while the whole chamber is set in the temperature range from 1,273 to 1,473 K. Growth process reactor geometry that involved with temperature distribution stabilization and uniformity control flow pattern between the substrate holder are discussed. It is seen that the flow pattern is influenced more by the temperature distribution and geometry of the chamber. The numerical study of horizontal MOHVPE growth shows a function of temperature and species flow rates has been performed with specific condition to find the ideal position of the substrate for growth process in future.